Evaluasi Perencanaan Kinerja Struktur Gedung Asrama 3 Lantai dengan Analisis Pushover - Ach Rizal Firmansyah; Suprapto Suprapto (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
Indonesia is located in one of the most active earthquake zones in the world. Earthquakes occur frequently, and one of them is in Malang City, which has had various impacts, including causing many casualties and completely destroying thousands of buildings. The impact of earthquakes on social and economic aspects is enormous. The purpose of this study is to present an overview of the performance of the 3 story dormitory building structure against earthquake threats. The method used to evaluate the structural performance of the building is pushover analysis. Pushover analysis is one of the performance-based design methods that evaluates critical points of the structure under earthquake loads by applying gradual loads until the target displacement is achieved. The analysis was conducted based on the SNI 1726 2019 standard and ATC-40 performance criteria, with structural modelling using ETABS. The results of the analysis are the capacity curve and the maximum total drift values: X= 0.0129 and Y= 0.014. Based on these results, the structural performance level is Damage Control (DC), meaning the building is safe during an earthquake, the risk of casualties and structural failure is not significant, and the building can be immediately reoccupied.